DoE Approach: A Stability Indicating RP-HPLC Method for Simultaneous Estimation of Methylparaben, Mometasone furoate and Eberconazole nitrate in Topical Formulations - Prakashkumar B. Modi & , Nehal J. Shah & (Journal of Applied Pharmaceutical Science, 2014)
A rapid and sensitive stability indicating RP-HPLC method is developed for the simultaneous estimation of Methylparaben, Mometasone Furoate and Eberconazole Nitrate in topical formulations. Chromatographic separation was achieved on Waters Xterra C18 (150 × 4.6 mm, 5µm) using a mobile phase constituted of water and methanol (35:65, v/v) at a flow rate of 1.50 mL/min and column temperature of 30ËšC. All three components were measured with uv detection at 235 nm. Force degradation study was conducted to determine Methylparaben, Mometasone Furoate and Eberconazole Nitrate in the presence of degradants and excipients peaks. Developed method was validated for method precision, specificity, linearity, accuracy, robustness and solution stability as per ICH guidelines. Method is showing linearity in the range of 0.25-188, 0.50-75 and 2.0-750 µg/mL for Methylparaben, Mometasone Furoate and Eberconazole Nitrate respectively. The method was proved to be robust by conducting DOE study. The method is suitable for stability studies, routine analysis and quality control of topical formulations containing these components, either alone or in combination.
Keywords: Methylparaben, Mometasone furoate, Eberconazole nitrate, Stability indicating, DoE.